Airflow and Power-Split Control Strategy for a Fuel Cell Hybrid Powered Robot. Issue 20 (2021) - Figueroa-Santos, Miriam; Sulzer, Valentin; Kim, Youngki; Siegel, Jason; Stefanopoulou, Anna; Rizzo, Denise M.
Abstract: Fuel cell control systems are designed to regulate temperature and reactant flow rates to ensure efficient electrochemical reactions and to avoid degradation and membrane failure from stack overheating. In air-cooled systems, the temperature is controlled by regulating the cathode airflow. In this study, a pseudo-spectral optimization method is applied to obtain an optimal power-split while considering the fuel cell's thermal dynamics to avoid stack overheating and minimize the hydrogen consumption for a hybrid electric vehicle. For future real-time implementation, a dual-loop proportional plus integral (PI) control strategy is proposed to regulate the airflow by following a fuel cell temperature reference, while another PI controller regulates the fuel cell current by tracking a reference battery State Of Charge (SOC). The proposed PI controller which follows a fixed temperature setpoint and a linearly depleting battery state of charge trajectory, based on the average power consummation and trip duration, can achieve 96% of the fuel savings of the optimum hydrogen consumption with full preview information.